The divergence of traditional Aboriginal and contemporary fire management practices on Wik traditional lands, Cape York Peninsula, Northern Australia. (17th January 2018) - Perry, Justin J.; Sinclair, Melissa; Wikmunea, Horace; Wolmby, Sidney; Martin, David; Martin, Bruce
Summary: Fire has been a critical component of Aboriginal culture and natural resource management in Australia for millennia. Aboriginal fire management in Northern Australia is widespread and, in some more remote areas, has continued relatively undisrupted despite widespread changes in tenure and land use. For the Wik people of Western Cape York, there has been a continued connection to their culture and traditional lands. Recently, Wik traditional owners have formed a ranger program which has secured funding to manage contemporary land management issues. This includes the landscape‐scale management of fire for biodiversity conservation and greenhouse gas abatement. Because the work is being conducted by Aboriginal people, with consent from traditional owners and on their traditional lands, there is an assumption that the activities are compatible with historical traditional land management and cultural practices. In this study, we use participatory action research to compare contemporary fire management with the current understanding of traditional Aboriginal fire management to assess objectively the compatibility of these two paradigms. We do this by combining the experience and understanding of traditional owners with anthropological and ecological perspectives. We find that contemporary fire management is applied across traditional cultural boundaries using methods such as aerial incendiaries. Financial incentives and contractual obligations associated with fire management are externally driven or include modern considerations such as the protection of infrastructure. In contrast, traditional fire management was the prerogative of traditional owners and was applied at fine scales for specific outcomes. Fire management was governed by rules that determined how people moved across the landscape and how resources were partitioned and shared. Supporting the implementation of Aboriginal burning alongside current fire management practices could lead to significant community engagement in such activities and is likely to have much better biodiversity and social outcomes.